The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1182/blood.2021012727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-risk cytogenetics on outcomes for children and young adults receiving CD19-directed CAR T-cell therapy

Abstract: Chimeric antigen receptor (CAR) T-cell therapy can induce durable remissions of relapsed/refractory B-acute lymphoblastic leukemia (ALL). However, case reports suggested differential outcomes mediated by leukemia cytogenetics. We identified children and young adults with relapsed/refractory CD19+ ALL/lymphoblastic lymphoma treated on 5 CD19-directed CAR T-cell (CTL019 or humanized CART19) clinical trials or with commercial tisagenlecleucel from April 2012 to April 2019. Patients were hierarchically categorized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…We hope that ongoing and future studies will shed further light upon the potential of FLT3CART to treat or perhaps even prevent these presently universally-fatal lineage-switch relapses. 15,17 Expanding upon the clinical potential of FLT3CART for patients with relapsed/refractory KMT2A-R ALL, we also report successful development of bispecific CD19xFLT3CART immunotherapy with at least equivalent preclinical activity to that of monovalent CD19CART and FLT3CART. Recent data from clinical phase 1 studies have demonstrated exciting promise of bispecific CD19xCD22 and CD19xCD20 CAR T cell immunotherapies for patients with relapsed/refractory B-ALL or lymphoma.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…We hope that ongoing and future studies will shed further light upon the potential of FLT3CART to treat or perhaps even prevent these presently universally-fatal lineage-switch relapses. 15,17 Expanding upon the clinical potential of FLT3CART for patients with relapsed/refractory KMT2A-R ALL, we also report successful development of bispecific CD19xFLT3CART immunotherapy with at least equivalent preclinical activity to that of monovalent CD19CART and FLT3CART. Recent data from clinical phase 1 studies have demonstrated exciting promise of bispecific CD19xCD22 and CD19xCD20 CAR T cell immunotherapies for patients with relapsed/refractory B-ALL or lymphoma.…”
Section: Discussionmentioning
confidence: 85%
“…However, given recent reporting of FLT3i resistance mechanisms in patients with FLT3-mutant AML, such TKI-based therapies may not be curative for all patients. 36 Patients with KMT2A-R ALL are also known to be at particularly high risk of lymphoid-tomyeloid lineage switch following CD19CART immunotherapy 15,17 when compared to conventional chemotherapy or immunotherapy with the CD19xCD3 bispecific T-cell engager blinatumomab. 37 This lineage switch predilection presents a unique barrier to cure of these highrisk patients via CD19CART, as well as an opportunity for alternative therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations